Quantifying 60 years of declining European eel (Anguilla anguilla L., 1758) fishery yields in Mediterranean coastal lagoons - Aalto, E; Terradez Mas, J; Schiavina, M; De Leo, G; CAPOCCIONI, FABRIZIO; LEONE, CHIARA; CICCOTTI, ELEONORA (ICES Journal of Marine Science, 2015)
The European eel Anguilla anguilla is thought to be in a multi-decadal decline across its range. Although its northern Atlantic sub-populations are well-studied, little is known about the historical trend and current status of eel stock in the Mediterranean Sea. To fill this gap, we gathered catch data for 86 lagoon fisheries in nine countries across the Mediterranean basin and analysed historical trends and geographical and environmental patterns. We found a region-wide decline in eel catch, beginning in the mid-1970s and exceeding the simultaneous decline in non-eel fisheries, as well as lower productivity in larger lagoons and those in the southern Mediterranean. Additionally, we developed a population dynamics model to provide a preliminary estimate of pristine, potential, and actual escapement of spawning adults (silver eels) across the Mediterranean basin under historical and current conditions. Model results suggest that current escapement is 35% of escapement at pristine biomass levels, ,40% target set by EC regulation 1100/2007. Furthermore, we estimate that a complete closure of lagoon fisheries would achieve 57% of pristine escapement under current recruitment levels. Though preliminary, this analysis represents a first step towards a full assessment of the role of the Mediterranean subpopulation in overall eel stock recovery.